Victor Papanek : designer for the real world - Clarke, Alison J. (Cambridge, Massachusetts ; London, England : The MIT Press, 2021)
"A cultural geneaology of the influence of Victor Papanek on the world of transdisciplinary design"--
Introduction -- 1. Design clinic: the early formation of a social designer -- 2. Seduction of the innocent: from bondage fetishism to Frank Lloyd Wright -- 3. Studio 44: mid-century California calling -- 4. The comprehensive designer: toward a new politics of design -- 5. From bionics to racial politics: the making of a cold war designer -- 6. Prescription for rebellion? From styrofoam domes to animatronic women -- 7. Northern lights: the allure of Nordic design activism -- 8. Design for the real world: a call to action -- 9. Pragmatism before politics: social design turns nomadic -- 10. After design for the real world -- Notes -- Index.
BIBINDX
Keywords: Papanek, Victor J; Papanek, Victor J. -- Influence; Industrial designers -- United States -- Biography; Industrial design -- Social aspects